2019
DOI: 10.1111/vco.12520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ibrutinib on proliferation and histamine release in canine neoplastic mast cells

Abstract: The Bruton's tyrosine kinase (BTK) inhibitor ibrutinib is effective in the treatment of human chronic lymphocytic leukaemia and mantle cell lymphoma. Recent data have shown that ibrutinib also blocks IgE‐dependent activation and histamine release in human basophils (BAs) and mast cells (MCs). The aim of this study was to investigate whether BTK serves as a novel therapeutic target in canine mast cell tumours (MCTs). We evaluated the effects of ibrutinib on two canine MC lines, C2 and NI‐1 and on primary MCs ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
(94 reference statements)
0
7
1
Order By: Relevance
“…At this time, there is no evidence to suggest that BTKis deplete mast cells or otherwise stunt their maturation. Prior studies found that ibrutinib can reduce the survival and proliferation of canine mast cell lines and canine neoplastic mast cells [ 53 ]; however, our own (unpublished) data found no differences in proliferation or survival of human skin-derived mast cells after treatment with ibrutinib, tirabrutinib, or acalabrutinib. In vivo data in food allergic adults and humanized mice demonstrate reversibility of BTKis’ effects after short courses (up to seven days of treatment) [ 9 ••, 21 ••], suggesting that, at least during short-term use, BTKis are unlikely to affect mast cell survival in vivo.…”
Section: Safety and Further Considerationscontrasting
confidence: 61%
“…At this time, there is no evidence to suggest that BTKis deplete mast cells or otherwise stunt their maturation. Prior studies found that ibrutinib can reduce the survival and proliferation of canine mast cell lines and canine neoplastic mast cells [ 53 ]; however, our own (unpublished) data found no differences in proliferation or survival of human skin-derived mast cells after treatment with ibrutinib, tirabrutinib, or acalabrutinib. In vivo data in food allergic adults and humanized mice demonstrate reversibility of BTKis’ effects after short courses (up to seven days of treatment) [ 9 ••, 21 ••], suggesting that, at least during short-term use, BTKis are unlikely to affect mast cell survival in vivo.…”
Section: Safety and Further Considerationscontrasting
confidence: 61%
“…We and others have previously shown that in vitro pretreatment of human basophils with the first-generation BTKi ibrutinib or the second-generation BTKi acalabrutinib abolishes their IgE-mediated activation (6,(12)(13)(14), and that 2 FDA-approved doses of ibrutinib prevents IgE-mediated basophil activation ex vivo (11). Prior studies have also demonstrated ibrutinib's ability to inhibit IgE-mediated degranulation in canine neoplastic mast cells (15). We therefore sought to investigate the effects of BTKis on IgE-mediated activation of human mast cells.…”
Section: Resultsmentioning
confidence: 97%
“…Among them, BTK and PI3K inhibitors have exhibited encouraging clinical results. On the one hand, the BTK inhibitor ibrutinib has significant value for the treatment of human DLBCL patients, particularly with ABC-DLBCL subtype [ 7 ], and has been shown to exert dose-dependent proliferation inhibition and IgE-dependent histamine release suppression in a pre-clinical model of canine mast cell tumor [ 21 ]. Further, although ibrutinib has not yet been approved for veterinary medicine, a dose-escalation study has been performed in dogs [ 22 ].…”
Section: Discussionmentioning
confidence: 99%